Contesting Welfare Discourses in Post-New Order Indonesia - Dimpos Manalu (PCD Journal, 2020)
This article analyses the contestation of 'welfare' discourses in Indonesia since the fall of the New Order, employing the discourse theory offered by Ernesto Laclau and Chantal Mouffe in their Hegemony and Socialist Strategy (2001 [1985]). Its main argument is that welfare is an “empty signifier”, the meaning of which may shift or change as a consequence of the unfinished discursive contestations of various subject positions. This article identifies four central discourses, or master signifiers, between 1998 and 2015 that serve as “nodal points” in the hegemonisation of welfare: "Social Safety Net", "Creative Innovation" versus "Electoral Strategy", "Sustainable Development", and "Right of the People and Constitutional Obligation of the State". The dominant and hegemonic meaning of welfare, understood here as a “nodal point”, is only temporary; it is partially fixed, while at the same time experiencing ongoing discursive contestation. It is, is being, and will be subjected to unending dislocation.